Study and application of a high temperature foaming agent in anionic-nonionic system namely HDHP: A case study of shale gas wells in Dongsheng Block, Sichuan Basin - ZHANG Longsheng,WANG Weiheng (Youqicang pingjia yu kaifa)
The shale gas wells in Dongsheng Block of Sichuan Basin are in deep reservoirs with the maximum depth of 4 300 m, with high stratum temperature up to 140 ℃ and of high mass concentration of calcium and magnesium ions up to 2.8×10-3 kg/L. All these characteristics result in the low flowback fluid volume and poor effect of foaming agent. In order to solve these problems, the fatty alcohol polyoxyethylene lauryl ether sulfate sodium（AES）, fluorohexyl ethanol polyoxyethylene ether（FT）, modified silicone oil resin polyether（FM） and metal-chelator（EDTA-2Na） are adopted as the raw materials to prepare a high temperature foaming agent in anionic-nonionic system namely HDHP. According to the orthogonal experimental design, the effects of different ratio of AES, FT and FM on the foaming ability and foaming stability are studied, and the optimum addition are determined. The comprehensive performance of HDHP evaluated in the laboratory shows a good effect of temperature and calcium and magnesium ions resistance. In the test of three wells in Dongsheng Block, the average gas production per well has increased by 30 %. The results show that HDHP is suitable for the foam drainage technology of ultra-deep shale gas wells in Dongsheng Block, and has good popularization and application value.